Concerns and Structural Barriers Associated with WIC Participation among WIC‐Eligible Women. Issue 5 (9th March 2016) - Liu, Cindy H.; Liu, Heidi
Abstract: Objectives: To examine sociodemographic status, psychosocial concerns, and structural barriers associated with women's participation in the USDA's Women, Infants, and Children (WIC) program among those eligible for the program. Design and Sample: A total of 1, 634 White, African‐American, Hispanic, and Asian/Pacific Islander (A/PI) women from the New York City area completed the Pregnancy Risk Assessment Monitoring System (PRAMS) from 2004 to 2007, a population‐based survey. Measures: Data on WIC eligibility and participation, sociodemographic details, unintended pregnancy, social support, and structural barriers were evaluated. Results: Hispanics and Blacks were 4.1 and 2.4 times more likely to participate, respectively, in the WIC program relative to Whites. Mothers reporting unplanned pregnancies, fewer social supports, and more structural barriers (e.g., transportation) were less likely to participate in WIC. Race‐stratified analyses revealed race/ethnic differences in the pattern of barriers; unintended pregnancy and structural problems were barriers associated with WIC participation particularly for A/PI. Conclusions: WIC‐eligible women with unintended pregnancies and fewer social supports tend to participate in WIC, but those who experience more structural barriers are less likely to participate. A/PI women may face specific challenges to WIC participation. Careful attention is needed to understand the unique attitudes and behaviors in the process of participating in WIC.